BESARAN KONTRIBUSI PRODUKSI HUTAN RAKYAT BERBASIS AGROFORESTRI TERHADAP PENDAPATAN PETANI DI DESA TELAGA LANGSAT KECAMATAN TAKISUNG - Deny Aprilliyanto; Daniel Itta; Mahrus Aryadi (Jurnal Sylva Scienteae, 2020)
Community forest was initially known through the karangkitri program which was built with the aim of greening the fields, talun and lands. The application of agroforestry is carried out using ecosystem modification practies that aim to conseve and multiply beneficial tree speies. Research to identifying community forest products based on agroforestry and calculate the contribution of the community forest.The object of this study is the farmers forest group who manage the agroforestry-based community forests in the village Telaga Langsat Sub-District Takisung.. Contribution data is calculated by manual calculation. The result of identification of community forest based on agroforestry in Telaga Langsat Village there are people forest product that is chicken farm, cattle farm, goat farm, honey bee farm. Horticultural products are rice, leek, chilli, yam, peanut and palm oil. The result of the plantation is rubber. The result of agroforestry in Telaga Langsat Village, Sub-District Takisung contributed 55.8% of total household income with average income of Rp.18.942.857 per year.Keyword: Forest people; agroforestry;contribution production